Gallic Acid Potentiates the Antimicrobial Activity of Tulathromycin Against Two Key Bovine Respiratory Disease (BRD) Causing-Pathogens - Rajamanickam, Karthic; Yang, Jian; Sakharkar, Meena Kishore (Frontiers in Pharmacology, 2019)
Bovine respiratory disease (BRD) is the most common infectious disease in dairy and beef cattle. It is associated with significant morbidity and mortality and causes a huge economic loss each year. In western Canada, a one-time injection of tulathromycin is commonly used as a metaphylactic procedure to reduce BRD incidence and eliminate potential BRD outbreak. With increased global concern on antibiotic usage in dairy and beef products and bacterial resistance to antibiotics, it is important to develop a novel strategy to eliminate the usage or decrease the dosage of antibiotics. In this study, we showed that gallic acid was active against both Mannheimia haemolytica and Pasteurella multocida, two key BRD causing-pathogens, with the minimum inhibitory concentration (MIC) measured at 250 g/mL and 500 g/mL, respectively. Co-administration of tulathromycin and gallic acid exhibited a strong additive or weak synergistic effect towards both M. haemolytic and P. multocida. Tulathromycin, gallic acid and their combination were also effective against the co-culture of M. haemolytic and P. multocida. Furthermore, we showed that pre-exposure to tulathromycin generated bacterial resistance to the antibiotic in M. haemolytica but not in P. multocida.